Tools for understanding the agricultural production systems and their socio-economic context in target regions for the introduction of new banana cultivars: Seasonal calendar focus group discussion - Crichton, R.; Albertson, E.; Caron, Cynthia M.; Bergh, Inge van den (Bioversity International, 2018)
Within the framework of the IITA-led project “Improvement of banana for smallholder farmers in the Great Lakes region of Africa” (also known as the “Breeding Better Bananas” project, http://breedingbetterbananas.org), Bioversity International and partners conducted baseline research in the target regions of Luwero and Mbarara in Uganda, and Bukoba, Meru, Moshi and Rungwe in Tanzania during 2015-2016, prior to conducting on-station and on-farm evaluations of the new NARITA banana cultivars.